The Effect of Enterprise Risk Management Based on Iso 31000 Company Performance According to An Islamic Business Perspective (Study on Pt Pln Nusantara Power up Tarahan) - Dewi Ayu Rahmawati; Siska Yuli Anita; Oza Restianita (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
The electricity sector faces significant challenges related to operational risks, efficiency, and energy supply reliability. This situation demands an integrated and sustainable risk management system. PT PLN Nusantara Power UP Tarahan, as one of the power generation units in Sumatra, has a high urgency to strengthen its risk governance system through the implementation of Enterprise Risk Management (ERM) based on ISO 31000. In addition, the application of Islamic Business Values such as trustworthiness (amanah), honesty (shiddiq), and justice (‘adl) is expected to enhance integrity and ethical culture within the organization. This study aims to analyze the effect of Enterprise Risk Management (ERM) based on ISO 31000 on Corporate Performance, as well as to examine its implementation from an Islamic Business Perspective at PT PLN Nusantara Power UP Tarahan. The research employed a quantitative explanatory approach involving 31 respondents selected through purposive sampling, supported by interviews with the Quality, Risk, and Compliance Management Department. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 software. The results indicate that all constructs were valid and reliable, with outer loading values > 0.70, Cronbach’s Alpha ranging from 0.781 to 0.951, Composite Reliability from 0.872 to 0.962, and Average Variance Extracted (AVE) from 0.620 to 0.836. Empirically, Enterprise Risk Management has a positive and significant effect on Corporate Performance (T-statistics > 1.96; P-value < 0.05). ISO 31000 has a positive and significant impact on ERM, but it does not have a direct effect on Corporate Performance. In contrast, the Islamic Business Perspective has a positive but insignificant effect on Corporate Performance